Impact evaluation of the efficacy of different doses of vitamin D supplementation during pregnancy on pregnancy and birth outcomes: a randomised, controlled, dose comparison trial in Pakistan. Issue 2 (27th September 2021) - Nausheen, Sidrah; Habib, Atif; Bhura, Maria; Rizvi, Arjumand; Shaheen, Fariha; Begum, Kehkashan; Iqbal, Junaid; Ariff, Shabina; Shaikh, Lumaan; Raza, Syed Shamim; Soofi, Sajid Bashir
Abstract : Background: Vitamin D deficiency during pregnancy is a public health problem in Pakistan and is prevalent among most women of reproductive age in the country. Vitamin D supplementation during pregnancy is suggested to prevent adverse pregnancy outcomes and vitamin D deficiency in both the mother and her newborn. Methods: We conducted a double-blinded, randomised controlled trial in Karachi, Pakistan to evaluate the effect of different doses of vitamin D supplementation during pregnancy on biochemical markers (serum 25(OH)D, calcium, phosphorus and alkaline phosphatase) in women and neonates, and on pregnancy and birth outcomes (gestational diabetes, pre-eclampsia, low birth weight, preterm births and stillbirths). Results: Pregnant women (N=350) in their first trimester were recruited and randomised to three treatment groups of vitamin D supplementation: 4000 IU/day (group A, n=120), 2000 IU/day (group B, n=115) or 400 IU/day (group C, n=115). Women and their newborn in group A had the lowest vitamin D deficiency at endline (endline: 75.9%; neonatal: 64.9%), followed by group B (endline: 84.9%; neonatal: 73.7%) and then the control group (endline: 90.2%; neonatal: 91.8%). Vitamin D deficiency was significantly lower in group A than in group C (p=0.006) among women at endline and lower in both groups A and B than in the control group (p=0.001) in neonates. Within groups, serum 25(OH)D was significantly higher between baseline and endline in group A and between maternal baseline and neonatal levels in groups A and B. Participant serum 25(OH)D levels at the end of the trial were positively correlated with those in intervention group A (4000 IU/day) (β=4.16, 95% CI 1.6 to 6.7, p=0.002), with food group consumption (β=0.95, 95% CI 0.01 to 1.89, p=0.047) and with baseline levels of serum 25(OH)D (β=0.43, 95% CI 0.29 to 0.58, p<0.0001). Conclusion: The evidence provided in our study indicates that vitamin D supplementation of 4000 IU/day was more effective in reducing vitamin D deficiency among pregnant women and in improving serum 25(OH)D levels in mothers and their neonates compared with 2000 IU/day and 400 IU/day. Trial registration number NCT02215213 .